2003
DOI: 10.1007/bf03006675
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of99mTc-hexamethylpropyleneamineoxime white blood cell scintigraphy in a patient with eosinophilic gastroenteritis

Abstract: White blood cell (WBC) 99mTc-hexamethylpropyleneamineoxime (HMPAO) scintigraphy was performed in a patient with eosinophilic gastroenteritis. WBC accumulation was detected in the terminal ileum to descending colon, and pathological studies demonstrated eosinophilic infiltration at the same region. 99mTc-HMPAO-WBC scintigraphy was proved to be a useful tool for the detection of eosinophilic infiltration in eosinophilic gastroenteritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…In patients presenting with antral eosinophilic gastritis, a string sign may be seen as a sign of gastric outlet obstruction [51]. A few studies have reported the usefulness of Tc-99m hexamethylpropyleneamine oxime (HMPAO) scintigraphy scanning in detection of active eosinophilic inflammation, extent of disease, and assessment of the response to treatment [72,73].…”
Section: Radiographic Evaluationmentioning
confidence: 99%
“…In patients presenting with antral eosinophilic gastritis, a string sign may be seen as a sign of gastric outlet obstruction [51]. A few studies have reported the usefulness of Tc-99m hexamethylpropyleneamine oxime (HMPAO) scintigraphy scanning in detection of active eosinophilic inflammation, extent of disease, and assessment of the response to treatment [72,73].…”
Section: Radiographic Evaluationmentioning
confidence: 99%
“…A “halo sign” and “araneid limb–like sign” can be observed on CT as secondary to bowel-wall layering, and both can help in differentiating between an inflammatory and neoplastic lesion 64,65. Radioisotope scan with technetium ( 99m Tc) hexamethylpropyleneamineoxime–labeled white blood cells provides a useful tool in assessing the extent of the disease and monitoring therapeutic response, but has little diagnostic value, as this method does not differentiate EGE from other causes of intestinal inflammation 66,67…”
Section: Diagnosismentioning
confidence: 99%
“…This method allows for the assessment of the disease process advancement in a given tissue, based on the increased recruitment of lymphocytes to the sites of active inflammation. However, it does not enable differentiation of the cause of inflammation; moreover, its availability is significantly limited, which makes it of no value in the diagnostic process of EGE [15][16][17][18][19].…”
Section: Radiological Diagnosticsmentioning
confidence: 99%